The Effect Of Peroxisome Proliferatorr Activated Receptor Gamma (Pparγ) On The Expression Of Foxp3, Tigit, Icos And Histone Proteins In Natural T-Regulatory Cells - Lee, Pei Chen (2019)
Natural T Regulatory (nTreg) cells represent approximately 8-10% of the total CD4+ T cell population. These cells are crucial for immune homeostasis and autoimmunity prevention. Previous study showed that peroxisome proliferator-activated receptor gamma (PPARγ) ligands suppress Forkhead box P3 (FoxP3) expression in nTreg cells following 72 hours in vitro culture. Current study was performed to elucidate the effects of PPARγ ligands on T cell immunoreceptor with Ig and ITIM domains (TIGIT) and Inducible T cell costimulator (ICOS) expressions in activated nTreg cells isolated from Balb/c mice. We also focused on histone modifications on FoxP3 gene expression in activated nTreg cells following PPARγ ligand, 15-Deoxy-△(12,14)-prostaglandin J2 (15d-PGJ2) and its inhibitor, GW9662 treatment in type 1 diabetes (T1D) mouse model. Spleens of Balb/c, NOD and NOR mice were harvested through cervical dislocation. CD4+CD25+ cells were isolated using MoFlow automated sorter or Magnetic-activated cell sorting (MACS) magnetic separation and purity was analyzed by flow cytometry method. Isolated CD4+CD25+ cells were cultured for 72 hours in supplemented RPMI in the presence of anti-CD3/CD28 antibodies and IL-2 cytokine. In Balb/c mice, sorted cells treated with or without 15d-PGJ2 or ciglitazone for TIGIT and ICOS surface marker profiling. In NOD/NOR mice, isolated cells were treated with 15d-PGJ2 or ciglitazone with or without GW9662 inhibitor.